CAMI: Web-Based Application to Test Validity and Reliability of Research Instruments - Ovan Ovan; Andika Saputra (STKIP Singkawang, 2020)
Testing research instruments can be done using several applications such as SPSS, AMOS, Lisrell, and several other applications. However, the use of these applications encounters several obstacles for its users, the first is that some of these applications are paid, the costs that are not small to buy a license for this application often force users to use a pirated version of the application, which of course is detrimental for developers and tarnish the world of education itself. And the second is that the use of this application sometimes confuses the users, the cause is that the items in the application are too complex, making it difficult to use, and in some applications, there are demands that users have an understanding of programming to be able to use the application. Therefore, in this research, a web-based application was developed to test the validity and reliability of research instruments that are free of charge and easy to use by academics and researchers (this application is then called CAMI). The stages taken in this research are the study of the theory of testing the validity and reliability of the research instrument, collecting data, compiling the syntax for making applications, installing applications on a web server (so that they can be accessed online), and testing applications from the data obtained. The data used in this research is secondary data obtained from theses and journals. Furthermore, the data is used to test the web application that has been created, then the results of the test data output are compared with the test results using the SPSS application with the same data. From the test results, it was found that both validity and reliability tests gave the same output 100% as the SPSS application.